A hollow core-shell nanosphere composite graphite felt for vanadium battery and preparation method thereof
By combining hollow core-shell nanospheres and a variety of substances that inhibit oxygen evolution side reactions on the graphite felt electrode of all vanadium flow battery, the problems of low electrode activity and serious oxygen evolution side reactions are solved, and the circulation efficiency of the battery is significantly improved and electrolyte utilization rate.
Patent Information
- Application Number
- CN202411463287.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-21
AI Technical Summary
The graphite felt electrode of the all-vanadium flow battery has low electrochemical activity and high initial installation cost, and the redox potential on the positive electrode side overlaps with the potential of the oxygen evolution side reaction, resulting in a degradation of battery performance.
The hollow core-shell nanospheres were self-assembled and synthesized layer by layer by layer by layer, and the graphite felt was composited to improve the effective reactive area of the electrode, and a variety of substances such as SiO2 and TiO2 were composited on the graphite felt electrode to inhibit the side reaction of oxygen evolution.
The reaction activity of graphite felt electrodes and the charge and discharge cycle efficiency of vanadium batteries are significantly improved, the side reaction of oxygen evolution is effectively suppressed, the energy loss during battery operation is reduced, and the efficiency of the battery and the utilization rate of the electrolyte are improved.
Smart Images

Figure CN119050382B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of all-vanadium liquid flow battery electrodes, and in particular to a hollow core-shell nanosphere composite graphite felt for a vanadium battery and a preparation method thereof. Background Art
[0002] Among various flow batteries, all-vanadium flow batteries (vanadium batteries for short) are considered to be one of the most promising large-scale energy storage batteries because they reduce the impact of cross-contamination between positive and negative electrode materials, have high electrochemical reversibility, and greatly extend the service life of the electrolyte.
[0003] However, the graphite felt electrodes commonly used in all-vanadium flow batteries have low electrochemical activity and high initial installation costs of vanadium electrolytes, which still limit the commercial application of vanadium batteries. In order to improve the activity of graphite felt electrodes, the surface area of the electrode can be increased by introducing oxygen-containing functional groups on the surface of graphite felt, thereby improving the electrochemical activity of the positive electrode graphite felt electrode. However, since the redox potential on the positive electrode side of the vanadium battery overlaps with the potential of the oxygen evolution side reaction, the oxygen evolution side reaction will gradually intensify as the battery runs, thereby affecting the performance of the battery. Summary of the invention
[0004] In order to solve the above-mentioned technical problems, the present invention provides a hollow core-shell nanosphere composite graphite felt for vanadium batteries and a preparation method thereof.
[0005] A method for preparing a hollow core-shell nanosphere composite graphite felt for a vanadium battery comprises the following steps:
[0006] Step S1: placing a blank graphite felt in an atmosphere furnace for heat treatment, washing the treated graphite felt with dilute hydrochloric acid and ultrapure water, and drying to obtain pretreated graphite felt;
[0007] Step S2: 2-5 parts by volume of an alcohol reagent and 1 part by volume of ultrapure water are uniformly mixed, 1 part by volume of ethyl silicate is added, and the mixture is stirred to obtain a silane solution, and an alkali solution is added at a certain rate to adjust the pH value of the silane solution to 6.8-7.5, and stirring is continued during the process to obtain a silica sol;
[0008] Step S3: 3-8 parts by volume of a titanium source organic solvent and 1 part by volume of an alcohol reagent are mixed to obtain a solution A; 2-4 parts by volume of glacial acetic acid, 2-4 parts by volume of a titanium hydrolysis inhibitor and 1 part by volume of an alcohol reagent are mixed to obtain a solution B; the solution B is added to the solution A at a rate of (0.5-1) parts by volume / min, the pH value of the solution is adjusted to 3-5, stirred for 30 minutes, and then 1 part by volume of ultrapure water is added, stirred into a light yellow transparent solution, to obtain a titanium dioxide sol;
[0009] Step S4: adding the titanium dioxide sol to the silicon dioxide sol prepared in step S2 at a rate of (0.5-1) volume parts / min, stirring for 20-60 minutes, and cooling to room temperature to obtain titanium dioxide@silica sol;
[0010] Step S5, adding the metal salt solution to the titanium dioxide @ silicon dioxide sol prepared in step S3 at a rate of (0.5-1) volume parts / min, stirring for 1-3 hours, and obtaining a gel; placing the gel in a forced air drying oven to dry, obtaining a precursor powder, and placing the precursor powder in a muffle furnace to calcine, and obtaining metal oxide @ titanium dioxide @ silicon dioxide hollow core-shell nanospheres;
[0011] Step S6, dispersing the metal oxide @ titanium dioxide @ silicon dioxide hollow core-shell nanospheres into 1 volume portion of a 5wt% perfluorosulfonic acid resin solution to obtain an impregnation solution; placing the pretreated graphite felt in the impregnation solution for physical impregnation, and drying to obtain a hollow core-shell nanosphere composite graphite felt.
[0012] Preferably, the heat treatment method in step S1 is: under nitrogen protection, heating to 400-500° C. at a rate of 4-10° C. / min, and keeping the temperature for 2-6 hours.
[0013] Preferably, in step S2, the stirring temperature is 30-40° C.; the rate of adding the alkaline solution is (0.05-0.1) parts by volume / min; the alkaline solution is one of sodium hydroxide, potassium hydroxide, and ammonia water, and the concentration is 1-3 mol / L.
[0014] Preferably, the alcohol reagent in step S2 and step S3 is the same substance, selected from one of anhydrous ethanol, propanol and isopropanol.
[0015] Preferably, in step S3, the titanium source organic solvent is one of tetrabutyl titanate and isopropyl titanate; the titanium hydrolysis inhibitor is one of glacial acetic acid, nitric acid, acetylacetone, triethanolamine, and diethanolamine.
[0016] Preferably, the metal salt solution in step S5 is one of zinc acetate solution, zirconium acetate solution, manganese acetate solution, niobium acetate solution, and tin acetate solution, with a concentration of 1-3 mol / L, and the concentration and addition amount are equal to the concentration and addition amount of the alkaline solution in S2; the drying temperature is 50-100° C., and the drying time is 6-12 h.
[0017] Preferably, the calcination process is: calcining at 450-600°C for 2-6h in an air atmosphere, with a heating rate of 5-10°C / min and a cooling rate of 3-5°C / min until the temperature drops to 25°C.
[0018] Preferably, the same stirring temperature is used in step S3, step S4 and step S5, and the stirring temperature is 50-70°C.
[0019] Preferably, in step S6, the physical immersion time is 12-24 hours, and the physical immersion temperature is 20-60°C.
[0020] A hollow core-shell nanosphere composite graphite felt for vanadium battery is prepared by adopting the method for preparing the hollow core-shell nanosphere composite graphite felt for vanadium battery.
[0021] The beneficial effects of the present invention are:
[0022] 1. The hollow core-shell nanospheres synthesized by layer-by-layer self-assembly using the sol-gel method have a stable structure, a diameter of about 200-350nm, and a large active area. The composite with graphite felt can significantly increase the effective reaction active area of the graphite felt, improve the redox reaction kinetic rate of the vanadium battery, and thus improve the charge and discharge cycle efficiency of the battery;
[0023] 2. The present invention compounds SiO2, TiO2, ZnO, ZrO2, Mn3O4, Nb2O5, SnO2 and other substances capable of inhibiting the side reaction of oxygen evolution on the graphite felt electrode. Compared with the traditional single substance capable of inhibiting the side reaction of oxygen evolution, the present invention can more effectively inhibit the side reaction of oxygen evolution occurring on the positive electrode side of the vanadium battery, reduce the energy loss caused by the side reaction during the operation of the battery, and thus improve the efficiency of the battery and the utilization rate of the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 SEM image of the hollow core-shell nanospheres in Example 1 of the present invention;
[0025] Figure 2 LSV curves of oxygen evolution of the graphite felt electrode in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below through the accompanying drawings and embodiments. However, it should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.
[0027] A method for preparing a hollow core-shell nanosphere composite graphite felt for a vanadium battery comprises the following steps:
[0028] Step S1: placing a blank graphite felt in an atmosphere furnace for heat treatment, washing the treated graphite felt with dilute hydrochloric acid and ultrapure water, and drying to obtain pretreated graphite felt; the heat treatment method is: under nitrogen protection, heating to 400-500°C at a rate of 4-10°C / min, and keeping warm for 2-6h;
[0029] Step S2: 2-5 parts by volume of an alcohol reagent and 1 part by volume of ultrapure water are uniformly mixed, 1 part by volume of ethyl silicate is added, and the mixture is stirred to obtain a silane solution, and an alkali solution is added at a certain rate to adjust the pH value of the silane solution to 6.8-7.5, and stirring is continued during the period to obtain a silica sol; the stirring temperature is 30-40° C.; the alkali solution is added at a rate of (0.05-0.1) parts by volume / min; the alkali solution is one of sodium hydroxide, potassium hydroxide, and ammonia water, and the concentration is 1-3 mol / L; and the alkali solution is selected from one of anhydrous ethanol, propanol, and isopropanol;
[0030] Step S3: 3-8 parts by volume of a titanium source organic solvent and 1 part by volume of an alcohol reagent are mixed to obtain a solution A; 2-4 parts by volume of glacial acetic acid, 2-4 parts by volume of a titanium hydrolysis inhibitor and 1 part by volume of an alcohol reagent are mixed to obtain a solution B; the solution B is added to the solution A at a rate of (0.5-1) parts by volume / min, the pH value of the solution is adjusted to 3-5, stirred in a water bath at 50-70°C for 30 minutes, and then 1 part by volume of ultrapure water is added and stirred to form a light yellow transparent solution to obtain a titanium dioxide sol; selected from one of anhydrous ethanol, propanol and isopropanol; the titanium source organic solvent is one of tetrabutyl titanate and isopropyl titanate; the titanium hydrolysis inhibitor is one of nitric acid, acetylacetone, triethanolamine and diethanolamine;
[0031] Step S4: adding the titanium dioxide sol to the silicon dioxide sol prepared in step S2 at a rate of (0.5-1) volume parts / min, stirring in a water bath at 50-70° C. for 20-60 min, and cooling to room temperature to obtain titanium dioxide@silica sol;
[0032] Step S5, adding the metal salt solution to the titanium dioxide @ silicon dioxide sol prepared in step S3 at a rate of (0.5-1) volume parts / min, stirring in a water bath at 50-70°C for 1-3 hours to obtain a gel; drying the gel in a blast drying oven to obtain a precursor powder, calcining the precursor powder in a muffle furnace to obtain metal oxide @ titanium dioxide @ silicon dioxide hollow core-shell nanospheres; the metal salt solution is a zinc acetate solution, a zirconium acetate solution, a manganese acetate solution, a niobium acetate solution, a tin acetate solution One, the concentration is 1-3 mol / L, and the concentration and the amount added are kept equal to the concentration and the amount added of the alkaline solution in S2; the drying temperature is 50-100°C, and the drying time is 6-12 hours; the calcination process is: calcining at 450-600°C for 2-6 hours in an air atmosphere, the heating rate is 5-10°C / min, the cooling rate is 3-5°C / min, and the temperature is cooled to 25°C; the same stirring temperature is used in step S3, step S4, and step S5, and the stirring temperature is 50-70°C;
[0033] Step S6, dispersing the metal oxide @ titanium dioxide @ silicon dioxide hollow core-shell nanospheres into 1 volume portion of a 5wt% perfluorosulfonic acid resin solution to obtain an impregnation solution; placing the pretreated graphite felt in the impregnation solution for physical impregnation, and drying to obtain a hollow core-shell nanosphere composite graphite felt; the physical impregnation time is 12~24h, and the physical impregnation temperature is 20~60℃.
[0034] Embodiment 1: comprising the following steps
[0035] Step S1, graphite felt pretreatment: placing the graphite felt in an atmosphere furnace for heat treatment at 400°C for 4 hours, with a heating rate of 4°C / min, washing the treated graphite felt with 1 mol / L hydrochloric acid and ultrapure water, and drying in an oven at 50°C;
[0036] Step S2, preparation of silica sol: 2 parts by volume of anhydrous ethanol and 1 part by volume of ultrapure water were mixed evenly, 1 part by volume of ethyl silicate was added, and the mixture was stirred in a magnetic stirrer to obtain a silane solution, 1 mol / L sodium hydroxide was uniformly added at a rate of 0.05 parts by volume / min, and the pH value of the silane solution was adjusted to 6.8, and stirring was continued in a water bath at 30° C. to obtain SiO2 sol;
[0037] Step S3, preparation of titanium dioxide @ silicon dioxide sol: 3 parts by volume of tetrabutyl titanate and 1 part by volume of anhydrous ethanol are mixed to obtain solution A; 2 parts by volume of glacial acetic acid, 2 parts by volume of nitric acid and 1 part by volume of anhydrous ethanol are mixed to obtain solution B, solution B is uniformly added to solution A at a rate of 0.5 parts by volume / min, the pH value of the solution is adjusted to 3, stirred in a water bath at 50° C. for 30 minutes, and then 1 part by volume of ultrapure water is added, stirred to form a light yellow transparent solution, to obtain TiO2 sol;
[0038] Step S4, adding the prepared TiO2 sol to the SiO2 sol prepared in step S2 at a rate of 0.5 parts by volume / min, stirring for 60 minutes, and cooling to room temperature to obtain TiO2@SiO2 sol;
[0039] Step S5, preparation of metal oxide @ titanium dioxide @ silicon dioxide core-shell nanospheres: add 1 mol / L zinc acetate solution to the TiO2@SiO2 sol prepared in step S4 at a rate of 0.5 parts by volume / min, the added volume being equal to the sodium hydroxide in step S2, stirring for 3 hours to obtain a gel, placing it in a blast drying oven at 50°C for 12 hours to obtain a precursor powder, placing it in a muffle furnace and calcining it at 450°C for 6 hours, with a heating rate of 5°C / min and a cooling rate of 3°C / min to obtain ZnO@TiO2@SiO2 hollow core-shell nanospheres;
[0040] Step S6, preparation of composite graphite felt electrode: disperse the nanospheres in 5wt% perfluorosulfonic acid resin solution to obtain an impregnation solution; place the pretreated graphite felt in the impregnation solution, soak it at 20°C for 24h, and dry it in a 50°C oven after impregnation to obtain a hollow core-shell nanosphere composite graphite felt electrode.
[0041] Embodiment 2: comprising the following steps
[0042] Step S1, graphite felt pretreatment: placing the graphite felt in an atmosphere furnace for heat treatment at 425°C for 3.5h, with a heating rate of 5°C / min, washing the treated graphite felt with 1mol / L hydrochloric acid and ultrapure water, and drying in an oven at 50°C;
[0043] Step S2, preparation of silica sol: 3 parts by volume of anhydrous ethanol and 1 part by volume of ultrapure water were mixed evenly, 1 part by volume of ethyl silicate was added, and the mixture was stirred in a magnetic stirrer to obtain a silane solution, 2 mol / L sodium hydroxide was uniformly added at a rate of 0.05 parts by volume / min, and the pH value of the silane solution was adjusted to 7, and the mixture was stirred in a water bath at 30° C. to obtain SiO2 sol;
[0044] Step S3, preparation of titanium dioxide @ silicon dioxide sol: 4 parts by volume of tetrabutyl titanate and 1 part by volume of anhydrous ethanol are mixed to obtain solution A; 2 parts by volume of glacial acetic acid, 2 parts by volume of nitric acid and 1 part by volume of anhydrous ethanol are mixed to obtain solution B, solution B is uniformly added to solution A at a rate of 0.5 parts by volume / min, the pH value of the solution is adjusted to 3, stirred in a water bath at 55° C. for 30 minutes, and then 1 part by volume of ultrapure water is added, stirred to form a light yellow transparent solution, to obtain TiO2 sol;
[0045] Step S4, adding the prepared TiO2 sol to the SiO2 sol prepared in step S2 at a rate of 0.5 parts by volume / min, stirring for 50 minutes, and cooling to room temperature to obtain TiO2@SiO2 sol;
[0046] Step S5, preparation of metal oxide @ titanium dioxide @ silicon dioxide core-shell nanospheres: add 2 mol / L zirconium acetate solution to the TiO2@SiO2 sol prepared in step S4 at a rate of 0.5 parts by volume / min, the added volume being equal to the sodium hydroxide in step S2, stirring for 2.5 hours to obtain a gel, placing it in a forced air drying oven at 60°C for 10 hours to obtain a precursor powder, placing it in a muffle furnace and calcining it at 500°C for 5 hours, with a heating rate of 6°C / min and a cooling rate of 3°C / min to obtain ZrO2@TiO2@SiO2 hollow core-shell nanospheres;
[0047] Step S6, preparation of composite graphite felt electrode: disperse the nanospheres in 5wt% perfluorosulfonic acid resin solution to obtain an impregnation solution; place the pretreated graphite felt in the impregnation solution, soak it at 20°C for 24h, and dry it in a 50°C oven after impregnation to obtain a hollow core-shell nanosphere composite graphite felt electrode.
[0048] Embodiment 3: comprising the following steps
[0049] Step S1, graphite felt pretreatment: placing the graphite felt in an atmosphere furnace for heat treatment at 450°C for 3h, with a heating rate of 6°C / min, washing the treated graphite felt with 1mol / L hydrochloric acid and ultrapure water, and drying in an oven at 50°C;
[0050] Step S2, preparation of silica sol: 4 parts by volume of propanol and 1 part by volume of ultrapure water were mixed evenly, 1 part by volume of ethyl silicate was added, and the mixture was stirred in a magnetic stirrer to obtain a silane solution, 3 mol / L ammonia water was uniformly added at a rate of 0.075 parts by volume / min, the pH value of the silane solution was adjusted to 7, and stirring was continued in a water bath at 35° C. to obtain SiO2 sol;
[0051] Step S3, preparation of titanium dioxide @ silicon dioxide sol: 5 parts by volume of tetrabutyl titanate and 1 part by volume of propanol are mixed to obtain solution A; 3 parts by volume of glacial acetic acid, 3 parts by volume of acetylacetone and 1 part by volume of propanol are mixed to obtain solution B, solution B is uniformly added to solution A at a rate of 0.75 parts by volume / min, the pH value of the solution is adjusted to 4, stirred in a water bath at 60° C. for 30 minutes, and then 1 part by volume of ultrapure water is added, stirred to form a light yellow transparent solution, to obtain TiO2 sol;
[0052] Step S4, adding the prepared TiO2 sol to the SiO2 sol prepared in step S2 at a rate of 0.75 parts by volume / min, stirring for 40 minutes, and cooling to room temperature to obtain TiO2@SiO2 sol;
[0053] Step S5, preparation of metal oxide @ titanium dioxide @ silicon dioxide core-shell nanospheres: add 3 mol / L manganese acetate solution to the TiO2@SiO2 sol prepared in step S4 at a rate of 0.75 parts by volume / min, the added volume being equal to the ammonia water in step S2, stirring for 2 hours to obtain a gel, placing it in a forced air drying oven at 70°C for 9 hours to obtain a precursor powder, placing it in a muffle furnace and calcining it at 520°C for 4 hours, with a heating rate of 8°C / min and a cooling rate of 4°C / min to obtain Mn3O4@TiO2@SiO2 hollow core-shell nanospheres;
[0054] Step S5, preparation of composite graphite felt electrode: disperse the nanospheres in 5wt% perfluorosulfonic acid resin solution to obtain an impregnation solution; place the pretreated graphite felt in the impregnation solution, soak it at 40°C for 18h, and dry it in a 50°C oven after impregnation to obtain a hollow core-shell nanosphere composite graphite felt electrode.
[0055] Embodiment 4: comprising the following steps
[0056] Step S1, graphite felt pretreatment: placing the graphite felt in an atmosphere furnace for heat treatment at 480°C for 2.5h, with a heating rate of 8°C / min, washing the treated graphite felt with 1mol / L hydrochloric acid and ultrapure water, and drying in an oven at 50°C;
[0057] Step S2, preparation of silica sol: 4.5 parts by volume of isopropanol and 1 part by volume of ultrapure water were mixed evenly, 1 part by volume of ethyl silicate was added, and the mixture was stirred in a magnetic stirrer to obtain a silane solution, 3 mol / L ammonia water was uniformly added at a rate of 0.075 parts by volume / min, the pH value of the silane solution was adjusted to 7, and stirring was continued in a water bath at 35° C. to obtain SiO2 sol;
[0058] Step S3, preparation of titanium dioxide @ silicon dioxide sol: 6 parts by volume of isopropyl titanate and 1 part by volume of isopropanol are mixed to obtain solution A; 3 parts by volume of glacial acetic acid, 3 parts by volume of triethanolamine and 1 part by volume of isopropanol are mixed to obtain solution B, solution B is uniformly added to solution A at a rate of 0.75 parts by volume / min, the pH value of the solution is adjusted to 4, stirred in a water bath at 65°C for 30 minutes, and then 1 part by volume of ultrapure water is added, stirred to obtain a light yellow transparent solution, to obtain TiO2 sol;
[0059] Step S4, adding the prepared TiO2 sol to the SiO2 sol prepared in step S2 at a rate of 0.75 parts by volume / min, stirring for 30 minutes, and cooling to room temperature to obtain TiO2@SiO2 sol;
[0060] Step S5, preparation of metal oxide @ titanium dioxide @ silicon dioxide core-shell nanospheres: add 2 mol / L niobium acetate solution to the TiO2@SiO2 sol prepared in step S4 at a rate of 0.75 parts by volume / min, the added volume being equal to the ammonia water in step S2, stirring for 1.5 hours to obtain a gel, placing it in a forced air drying oven at 80°C for 7 hours to obtain a precursor powder, placing it in a muffle furnace and calcining it at 550°C for 3 hours, with a heating rate of 9°C / min and a cooling rate of 5°C / min to obtain Nb2O5@TiO2@SiO2 hollow core-shell nanospheres;
[0061] Step S5, preparation of composite graphite felt electrode: disperse the nanospheres in 5wt% perfluorosulfonic acid resin solution to obtain an impregnation solution; place the pretreated graphite felt in the impregnation solution, soak it at 50°C for 15h, and dry it in a 50°C oven after impregnation to obtain a hollow core-shell nanosphere composite graphite felt electrode.
[0062] Embodiment 5: comprising the following steps
[0063] Step S1, graphite felt pretreatment: placing the graphite felt in an atmosphere furnace for heat treatment at 500°C for 2h, with a heating rate of 10°C / min, washing the treated graphite felt with 1 mol / L hydrochloric acid and ultrapure water, and drying in an oven at 50°C;
[0064] Step S2, preparation of silica sol: 5 parts by volume of isopropanol and 1 part by volume of ultrapure water were mixed evenly, 1 part by volume of ethyl silicate was added, and the mixture was stirred in a magnetic stirrer to obtain a silane solution, 1 mol / L potassium hydroxide was uniformly added at a rate of 0.1 parts by volume / min, and the pH value of the silane solution was adjusted to 7.5, and stirring was continued in a water bath at 40° C. to obtain SiO2 sol;
[0065] Step S3, preparation of titanium dioxide @ silicon dioxide sol: 8 parts by volume of isopropyl titanate and 1 part by volume of isopropanol are mixed to obtain solution A; 4 parts by volume of glacial acetic acid, 4 parts by volume of diethanolamine and 1 part by volume of isopropanol are mixed to obtain solution B, solution B is uniformly added to solution A at a rate of 1 part by volume / min, the pH value of the solution is adjusted to 5, stirred in a water bath at 70°C for 30 minutes, and then 1 part by volume of ultrapure water is added, stirred to obtain a light yellow transparent solution, to obtain TiO2 sol;
[0066] Step S4, adding the prepared TiO2 sol to the SiO2 sol prepared in step S2 at a rate of 1 part by volume / min, stirring for 20 minutes, and cooling to room temperature to obtain TiO2@SiO2 sol;
[0067] Step S5, preparation of metal oxide @ titanium dioxide @ silicon dioxide core-shell nanospheres: add 1 mol / L tin acetate solution at a rate of 1 volume part / min to the TiO2@SiO2 sol prepared in step S4, the added volume being equal to the potassium hydroxide in step S2, stirring for 1 hour to obtain a gel, placing it in a forced air drying oven at 100°C for 6 hours to obtain a precursor powder, placing it in a muffle furnace at 600°C for calcination for 3 hours, with a heating rate of 10°C / min and a cooling rate of 5°C / min to obtain SnO2@TiO2@SiO2 hollow core-shell nanospheres;
[0068] Step S5, preparation of composite graphite felt electrode: disperse the nanospheres in 5wt% perfluorosulfonic acid resin solution to obtain an impregnation solution; place the pretreated graphite felt in the impregnation solution, soak it at 60°C for 12h, and dry it in a 50°C oven after impregnation to obtain a hollow core-shell nanosphere composite graphite felt electrode.
[0069] Comparative Example 1:
[0070] This comparative example is a blank control group, that is, blank graphite felt is used as the electrode.
[0071] Comparative Example 2:
[0072] The preparation process of this comparative example is different from that of Example 1 only in that steps S3 and S4 are not performed.
[0073] Comparative Example 3:
[0074] The preparation process of this comparative example is different from that of the embodiment only in that step S4 is not performed.
[0075] Comparative Example 4:
[0076] The preparation process of this comparative example is as follows: 2g commercial SiO2, 2g TiO2 and 2g ZnO are mixed and dispersed in a 5wt% perfluorosulfonic acid resin solution to obtain an impregnation solution; the pretreated graphite felt is placed in the impregnation solution and soaked at 30°C for 12h. After impregnation, it is placed in a muffle furnace at 400°C and calcined to obtain a physically sintered graphite felt electrode.
[0077] The graphite felts prepared in Examples 1-5 and Comparative Examples 1-4 were assembled into battery stacks and subjected to charge and discharge tests under the same test conditions, and the battery coulombic efficiency, voltage efficiency, energy efficiency, and discharge capacity were recorded. The test results are shown in Table 1:
[0078] Table 1 Test results of electrode performance of examples and comparative examples
[0079]
[0080] From Table 1 and Figure 2 It can be seen that compared with Comparative Examples 1-3, Examples 1-5 have higher energy efficiency and discharge capacity, indicating that the present invention effectively reduces the amount of oxygen released from the positive electrode electrolyte, inhibits the oxygen evolution side reaction, improves the utilization rate of the electrolyte, and reduces the energy loss caused by the side reaction during battery operation by compounding SiO2, TiO2 and multiple oxygen evolution inhibitors such as ZnO, ZrO2, Mn3O4, Nb2O5, and SnO2. Figure 1It can be seen that by comparing Examples 1-5 with Comparative Example 4, the present invention adopts the sol-gel method to synthesize hollow core-shell nanospheres by layer-by-layer self-assembly, and the structure is stable. Compared with simple physical sintering composite, the synergistic effect between the components is more obvious. The diameter of the prepared nanospheres is about 200-350nm, the effective active area is increased, and the specific surface area is increased by composite with graphite felt, thereby accelerating the kinetic process of vanadium redox reaction.
[0081] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing hollow core-shell nanosphere composite graphite felt for vanadium batteries, characterized in that: The steps include: Step S1: placing a blank graphite felt in an atmosphere furnace for heat treatment, washing the treated graphite felt with dilute hydrochloric acid and ultrapure water, and drying to obtain pretreated graphite felt; Step S2: 2-5 parts by volume of an alcohol reagent and 1 part by volume of ultrapure water are uniformly mixed, 1 part by volume of ethyl silicate is added, and the mixture is stirred to obtain a silane solution, and an alkali solution is added at a certain rate to adjust the pH value of the silane solution to 6.8-7.5, and stirring is continued during the process to obtain a silica sol; Step S3: 3-8 parts by volume of a titanium source organic solvent and 1 part by volume of an alcohol reagent are mixed to obtain a solution A; 2-4 parts by volume of glacial acetic acid, 2-4 parts by volume of a titanium hydrolysis inhibitor and 1 part by volume of an alcohol reagent are mixed to obtain a solution B; the solution B is added to the solution A at a rate of 0.5-1 parts by volume / min, the pH value of the solution is adjusted to 3-5, stirred for 30 minutes, and then 1 part by volume of ultrapure water is added, stirred into a light yellow transparent solution, to obtain a titanium dioxide sol; Step S4: adding the titanium dioxide sol to the silicon dioxide sol prepared in step S2 at a rate of 0.5 to 1 volume parts / min, stirring for 20 to 60 minutes, and cooling to room temperature to obtain titanium dioxide@silica sol; Step S5, adding a metal salt solution to the titanium dioxide @ silicon dioxide sol prepared in step S3 at a rate of 0.5 to 1 volume parts / min, stirring for 1 to 3 hours to obtain a gel; placing the gel in a blast drying oven to dry to obtain a precursor powder, placing the precursor powder in a muffle furnace for calcination to obtain metal oxide @ titanium dioxide @ silicon dioxide hollow core-shell nanospheres; the metal salt solution is one of zinc acetate solution, zirconium acetate solution, manganese acetate solution, niobium acetate solution, and tin acetate solution; Step S6, dispersing the metal oxide @ titanium dioxide @ silicon dioxide hollow core-shell nanospheres into 1 volume portion of a 5wt% perfluorosulfonic acid resin solution to obtain an impregnation solution; placing the pretreated graphite felt in the impregnation solution for physical impregnation, and drying to obtain a hollow core-shell nanosphere composite graphite felt.
2. The method for preparing a hollow core-shell nanosphere composite graphite felt for vanadium battery according to claim 1, characterized in that: The heat treatment method in step S1 is: under nitrogen protection, heating to 400-500° C. at a rate of 4-10° C. / min, and keeping the temperature for 2-6 hours.
3. The method for preparing a hollow core-shell nanosphere composite graphite felt for vanadium battery according to claim 1, characterized in that: In step S2, the stirring temperature is 30-40° C.; the rate of adding the alkaline solution is 0.05-0.1 parts by volume / min; the alkaline solution is one of sodium hydroxide, potassium hydroxide, and ammonia water, and the concentration is 1-3 mol / L.
4. The method for preparing a hollow core-shell nanosphere composite graphite felt for vanadium battery according to claim 1, characterized in that: The alcohol reagent in step S2 and step S3 is the same substance, selected from one of anhydrous ethanol, propanol and isopropanol.
5. The method for preparing a hollow core-shell nanosphere composite graphite felt for vanadium battery according to claim 1, characterized in that: In step S3, the titanium source organic solvent is one of tetrabutyl titanate and isopropyl titanate; the titanium hydrolysis inhibitor is one of glacial acetic acid, nitric acid, acetylacetone, triethanolamine, and diethanolamine.
6. The method for preparing a hollow core-shell nanosphere composite graphite felt for vanadium battery according to claim 1, characterized in that: The concentration of the metal salt solution in step S5 is 1-3 mol / L, and the concentration and the amount added are kept equal to the concentration and the amount added of the alkali solution in S2; the drying temperature is 50-100° C., and the drying time is 6-12 hours.
7. The method for preparing a hollow core-shell nanosphere composite graphite felt for vanadium battery according to claim 1, characterized in that: The calcination process in step S5 is: calcining at 450-600° C. for 2-6 hours in an air atmosphere, with a heating rate of 5-10° C. / min and a cooling rate of 3-5° C. / min until the temperature drops to 25° C.
8. The method for preparing a hollow core-shell nanosphere composite graphite felt for vanadium battery according to claim 1, characterized in that: The stirring temperature in step S3, step S4 and step S5 is the same, which is 50-70°C.
9. The method for preparing a hollow core-shell nanosphere composite graphite felt for vanadium battery according to claim 1, characterized in that: In step S6, the physical immersion time is 12-24 hours, and the physical immersion temperature is 20-60°C.
10. A hollow core-shell nanosphere composite graphite felt for vanadium battery, characterized in that: The composite graphite felt is prepared by the method for preparing the hollow core-shell nanosphere composite graphite felt for vanadium batteries as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Nanoporous selective sol-gel ceramic membranes, selective -membrane structures, and related methods
CN111867709A
KR20210069905A